Tejano Religion and Ethnicity : San Antonio, 1821-1860 - Matovina, Timothy, 1955- (Book collections on Project MUSE., 1995)
The first book-length treatment of the historical role of religion in a Mexican-origin community in the United States, this study covers three distinct periods in the emergence of Tejano religious and ethnic identity: the Mexican period (1811-1836), the Texas Republic (1836-1845), and the first decade and a half after annexation into the United States (1845-1860). Matovina's research demonstrates how theories of unilateral assimilation are inadequate for understanding the Tejano community, especially in comparison with the experiences of European immigrants to the United States. As residents of the southwestern United States continue to sort out the legacy of U.S. territorial expansion in the nineteenth century, studies like this one offer crucial understanding of the survival and resilience of Latino cultures in the United States. Tejano Religion and Ethnicity will be of interest to a broad popular and scholarly audience.